The Charm of Words in the Creation of Mirzo Kenjabek (Eurasian Journal of Humanities and Social Sciences, 2023)
In the article, in a special lyrical tone, as a master of the artistic word, the poems of the religious and educational poet Mirza Kenjabek are scientifically analyzed, and in the views of the poet, every inch of mother earth is accompanied by dear feelings. It should also be said that in the poet's work there are works written in the epic spirit, in which there is a harmony of broad knowledge and thinking, along with simplicity and proximity to common speech. In this, the poet does not follow the path of dry didacticism, but imposes a new poetic meaning on the meaning and content